Effect of Degree of Saturation on Consolidation Parameters of Fine-Grained Soils - Kamil Kayabalı; Deniz Yılmaz (Bulletin of the Mineral Research and Exploration)
Terzaghi (1943)'s theory of consolidation phenomenon has some limitations for unsaturated geological environments in nature. Additionally, soils are subjected to consolidation tests under partially saturation conditions. The scope of this study is to illustrate the effect of degree of saturation (Sr) on the consolidation parameters using remolded soil samples. For this purpose, swelling pressure, compression index (cc), re-compression index (cr), coefficient of consolidation (cv), and pre-consolidation stress (σp') were determined for the samples having different degrees of saturation and plasticity (PI). The consolidation parameters obtained from “undersaturated” remolded samples with varying degrees of saturation were compared with the consolidation parameters obtained from “fully saturated” remolded samples to illustrate which parameters of consolidation are affected most by the degree of saturation. The effect of swelling of partially saturated samples was eliminated prior to conducting oedometer tests.Results indicated a meaningful relationship between the compression index and the degree of saturation, though the relationship with the recompression index was less certain. Pre-consolidation stress generally decreased as saturation increased, while no definitive trend was observed between the degree of saturation and the consolidation coefficient. Overall, most consolidation parameters were found to be somewhat affected by the degree of saturation.